Reinforced photocatalytic reduction of CO2 to CO by a ternary metal oxide NiCo2O41. Issue 24 (28th June 2015) - Wang, Zhaoyu; Jiang, Min; Qin, Jiani; Zhou, Han; Ding, Zhengxin
<x xml:space="preserve">Abstract</x> NiCo2O4 was developed as an efficient, low-price, stable, and reusable cocatalyst for the deoxygenative reduction of CO2 to CO.